Asymmetric role of human capital and trade liberalization in the economic growth of Pakistan: Fresh evidence from the nonlinear analysis. Issue 3 (3rd April 2023) - Luqman, Muhammad; Soytas, Ugur
Abstract : Human capital and trade liberalization are playing a central role in growth theories. However, the link between human capital, trade liberalization, and economic growth remains a challenging question due to the inconclusive results of the previous studies. Paper contributes to this debate through asymmetric links among human capital, trade liberalization, and economic growth by incorporating labor and capital for Pakistan's economy by applying the nonlinear autoregressive distributed lag model. Results suggest that the positive and negative asymmetric impact of trade liberalization and human capital on growth substantially vary in the short and long run. In the long run, the increased trade liberalization hurts economic growth, while increased human capital has a minimal positive impact on economic growth in the short and long run. The implications of this paper are for economists and policymakers to strengthen the role of human capital and trade liberalization for Pakistan.